The Unique Side of Luscious Natural Soap Ads - LUTHFI IHWANUDIN IMANI; TM RAYHAN AL RASYID; Harry Tjahjodiningrat (Universitas Pendidikan Indonesia, 2021)
Advertising is a form of business of a company, organization, or individual that aims to provide a persuasive message by promoting and offering a service, product, or idea to the wider community through print, audio, visual media, or a combination of both, namely through video media. Audio visual. Video advertisements are often found on television and online media such as social media such as Instagram and YouTube platforms. Luscious Natural is a brand from Bandung that is engaged in the field of beauty and health. Luscious Natural produces goods in the form of soap bars and liquid for the face and body made from natural ingredients as the name suggests, which has a unique form of soap products, one example being a soap bar in the form of cakes and food. Apart from the shape, this brand also offers soap with a variety of colors and themes that are unique and look artsy visually that can be ordered specifically or custom. In dissecting this advertisement, the researcher uses qualitative research methods and uses the Applied Media Aesthetics approach proposed by Herbert Zettl to dissect the aesthetic and semiotic values contained in the advertisement on a scene-by-scene basis. It is hoped that with the results of this analysis, researchers and spectators can find and know values that are deeper in meaning and not only in terms of the context of their visual beauty.